EFEKTIFITAS INQUIRY TERBIMBING DAN INQUIRY BEBAS TERMODIFIKASI MELALUI EKSPERIMEN TERHADAP HASIL BELAJAR FISIKA DITINJAU DARI KEMAMPUAN AWAL, KREATIFITAS, KEMAMPUAN BERPIKIR ABSTRAK SISWA KELAS X SMA NEGERI 6 KOTA MADIUN TAHUN AJARAN 2010/2011 - Andista Candra Yusro; Farida Huriawati; Purwandari Purwandari (Jurnal Pendidikan, 2012)
The  objectives  of this reseach  are:  (1) to help  students  choose  the most  suitable  learning  method,  (2) to serve  qualified  learning  to pass the threshold  level, (3) to make up the average  students'  mark in physics.  The method  of the study is experiment  applied  on students  of Grade X, SMA 6 Madiun.  The sample  is taken  under  cluster-random   sampling  technique having  class  XC  and  XD.  Data  on  students'   achievement   are  taken  by cognitive   test,  those  of  prior  achievement   are  taken  by  documentation technique,   those   of  creativity   and  abstraction   skill  are  taken   by  test. Hypothetical  examination  is done under factorial  anava 2x2x2x2.The  results  show  that:  (1)  there  is a different   influence  between guided  inquiry and free-modified   inquiry technique  (0.005 < 0.05), (2) there is influence  of high and low prior achievement  (0.000  < 0.05), (3) there is influence  of high  and  low students'  creativity  (0.039  < 0.05),  (4) there  is influence  of high and low abstarction  skill  (0.014 < 0.05), (5) there is no interaction   between   guided   and free-modified     unquiry technique  with students'  prior achievement  (0.043 < 0.05), (6) there is interaction  between guided and free-modified   unquiry technique  with students' creativity  (0.043 < 0.05), (7) there  is interaction  between  guided  and free-modified    unquiry technique  with  students'  abstraction   skill  (0.032  < 0.05),  (8) there  is no interaction   between   guided   and free-modified     unquiry   technique   with students'  prior  achievement,   creativity   and  abstraction   skill  towards  the achievement  (0.595 > 0.05).